GIS as tools for monitoring the urban development in metropolitan region: A case of Klang Valley Region, Peninsular Malaysia - Yaakup, Ahris; Sulaiman, Susilawati; Musa, Nuha; Ahmad, Mohamed Jamil; Ibrahim, Mohd. Zakaria (2002)
The monitoring of urban land use change forms an integral part of the regional planning process whereby policies and strategic plans are reviewed and updated. This task typically involves the identification of emerging land use patterns which are normally linked with other planning statistics such as employment, housing and population before the full significance of land use change are apparent. This requires planning programme to be adapted during their implementation as and when incoming information requires such change. Among the myriad of urbanisation issues faced by the local authorities in Klang Valley region includes traffic congestion, provision of housing and amenities and declining environmental situation. With a rational planning approach, the quality of planning and decision making process can be substantially improved with valid data appropriately and efficiently handled. Against this background, this paper will discuss and demonstrates the design and development of a GIS database as well as the customised applications for planning and monitoring the development of the region. The database was designed and developed to support ten application modules namely built up area, green and recreational areas, traffic and urban transport, squatter and low-cost housing, environment, utilities and community services, industrial and commercial development, population and socioeconomic, tourism facilities and geohazard. This required as many as more than 100 map layers including base map, administrative boundary, physical characteristics, environmental quality, traffic and urban transport, green and recreational areas, public facilities and utilities. Above all the application and analysis, a user interface and modelling was developed to facilitate an easy and friendly use of the system. Lastly, a web-based GIS for Klang Valley was also developed to integrate the data set and to encourage data sharing between various agencies involve in shaping the urban environment in Klang Valley region.